catena-Poly[[(diaquazinc)-μ-3-carboxypyrazine-2-carboxylato-κ(4) N (1),O (2);N (4),O (3)] nitrate] - Starosta, Wojciech (International Union of Crystallography, 2011)
The crystal structure of the title compound, {[Zn(C(6)H(3)N(2)O(4))(H(2)O)(2)]NO(3)}(n), is built of zigzag cationic chains propagating in [010] with nitrate anions located in the space between the chains. The Zn(II) ion is coordinated by N and O atoms of two symmetry-related ligands in equatorial sites, and by two water O atoms at the axial sites of a distorted octahedron. One carboxylate group of the ligand remains protonated, serving as a donor in a short intramolecular O—H⋯O hydrogen bond. The coordinated water molecules are donors and the nitrate O atoms act as acceptors in a network of O—H⋯O hydrogen bonds.